CHARACTERISTICS OF KAMABOKO FROM CATFISH (CLARIAS GARIEPINUS) SURIMI PROCESSED WITH CARROT AND BEET ROOT AS FILLER AND NATURAL FOOD COLORANTS - Suryaningrum, Theresia Dwi; Irianto, Hari Eko; Ikasari, Diah (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2015)
The objective of the study was to investigate the effect of beet root and carrot as filler and natural food colourant on the chemical, physical and sensory properties of kamaboko. Kamaboko from catfish (Clarias gariepinus) surimi was processed with carrot (Daucus carota) and beet root (Beta vulgaris) at two concentrations (12 and 16% of surimi weight). Assesment was done on chemical (proximate, pH), physical (folding test, WHC, gel strength and breaking force) properties as well as sensory evaluation. The results showed that kamaboko gel processed using beet root had better performance than kamaboko gel processed using carrot. Kamaboko processed using beet root has protein content, folding test, water holding capacity, gel strength, breaking force, and sensory characteristics (appearance, colour, odor, texture, and taste) better than kamaboko processed with carrot. Increasing concentration of filler only affect on the gel strength and breaking force of kamaboko processed with beet root. The best characteristic of kamaboko was obtained from kamaboko processed using beet root with concentration of 12%. However, beet root was not recommended as colourant since the colour was not stable especially when stored at freezer.